REVITALISASI PEMASARAN ONLINE PADA SEKTOR PEMASARAN IKAN HIAS - Mustofa, Romy Faisal; Gustaman, Randy Fadillah; Paturocman, Iwan Ridwan; Khoirunisa, Nisa (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
The main object of this community service focuses on online marketing of ornamental fish products at Bagja Buana and Karyamas business institutions so that the community can use them to support marketing effectiveness. By marketing online, it is hoped that it will save costs and open up the market widely by taking advantage of the rapid development of information and communication technology today. There are many platforms that can be used as marketing opportunities, such as using social media, websites, YouTube, e-marketplace applications and so on. The main problems of the ornamental fish cultivator group in Kondangjajar Village, Cijulang District, Pangandaran Regency are (1) Good business management has not been implemented, if seen from business governance which is still conventional (2) Marketing techniques are still relatively simple, waiting for collectors to come to the location to pick up ornamental fish, (3) Financial administration is still simple, so proper and correct digital business bookkeeping is required. (4) Lack of knowledge about regulations in the ornamental fish business. That standards, technical regulations and conformity assessments also play an important role in increasing competitiveness and adding value to the implementation of this strategy.